2009
DOI: 10.1093/schbul/sbn190
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Processing in Schizophrenia: A Meta-analysis of Functional Neuroimaging Data

Abstract: A marked underrecruitment of the amygdala, accompanied by a substantial limitation in activation throughout a ventral temporal-basal ganglia-prefrontal cortex "social brain" system may be central to the difficulties patients experience when processing facial emotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
225
3
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(248 citation statements)
references
References 71 publications
17
225
3
3
Order By: Relevance
“…However, there was one main neural activation difference that distinguished the impaired TBI group from the HC group. Our TBI-I group had significantly less activation in the right fusiform gyrus compared to HCs during the facial affect recognition task, consistent with our a priori hypotheses and prior literature findings in autism and schizophrenia (Edwards et al 2002;Li et al 2010). Additionally, there was a trend suggesting that right fusiform gyrus activation for the TBI-N group was intermediate to that in the HC and TBI-I groups.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, there was one main neural activation difference that distinguished the impaired TBI group from the HC group. Our TBI-I group had significantly less activation in the right fusiform gyrus compared to HCs during the facial affect recognition task, consistent with our a priori hypotheses and prior literature findings in autism and schizophrenia (Edwards et al 2002;Li et al 2010). Additionally, there was a trend suggesting that right fusiform gyrus activation for the TBI-N group was intermediate to that in the HC and TBI-I groups.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, this groundwork enables functional and meaningful interpretations to be made from neuroimaging studies that aim to understand facial affect recognition deficits in populations with impairments to these areas. For instance, numerous neuroimaging studies have already investigated the neurobiological mechanisms underlying facial affect recognition impairments in people with autism and schizophrenia (Harms et al 2010;Li et al 2010). The most consistent finding across these studies has been reduced activation in the amygdala and fusiform gyrus during facial affect recognition tasks relative to controls (Harms et al 2010;Li et al 2010).…”
Section: Conceptual Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, an acceptable proxy may be to survey existing neuroimaging studies of emotion perception in psychosis [15,27,28], and interpret their findings within the context of attentional and interpretative biases. Facilitating this interpretation is a model of aberrant emotion perception in schizophrenia [29].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced angular gyrus activity in schizophrenia has been observed during facial emotion discrimination (Reske et al., 2009; Streit et al., 2001) or social cognition (Thakkar, Peterman, & Park, 2014). Patients with schizophrenia have also shown neural deficits in the fusiform gyrus during emotional face processing (Gur et al., 2002; Li, Chan, McAlonan, & Gong, 2010; Wolf et al., 2015). Consistent with these studies, we observed reduced angular and fusiform activity in patients induced by pictures which included human faces in various social situations.…”
Section: Discussionmentioning
confidence: 99%